Exploring issues of self-stigma in "Emily's Voices": a memoir of psychosis and recovery. Issue 2 (3rd April 2018) - Austin, Roz
ABSTRACT: "Emily's Voices" is Roz Austin's memoir of recovery from psychosis. She published it under a pseudonym (Emily Knoll) and changed identifying features for various reasons of confidentiality. As you will discover when you read extracts from the book, one of the main problems for people who struggle with mental health problems is that they experience stigma, and they can stigmatise themselves. This memoir tells Emily's story of her struggle with hearing voices and her journey through the mental health system. Emily's voices are distressing, but her therapist and close friends help her to challenge the voices, and to confront some of the self-stigma which she feels about being a voice-hearer. Emily must find a way of accepting that she hears voices, or she can't be in the world – but it's a confrontation that takes all of her new-found strength and resolve. "Emily's Voices" is available to buy from Amazon. Roz recently completed her PhD with Durham University's "Hearing the Voice" research project. Her survivor-researcher-led project explored emotional aspects of the experience of hearing voices in the English adult population.